Model Inovasi Pengembangan Kurikulum dan Pembelajaran PAI Era 4.0 - Pramodana, Dimas Raba; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (DIMAR: Jurnal Pendidikan Islam, 2024)
The development of the Islamic Religious Education (PAI) curriculum in the era of the Fourth Industrial Revolution (4.0) faces specific challenges, including limited technological infrastructure, varying levels of teacher competence, and the readiness of students to utilize digital tools. This study aims to identify and analyze innovative models for developing the PAI curriculum and learning approaches suitable for the 4.0 era, focusing on integrating technology and competency-based learning methodologies. The research employed a qualitative approach with a case study design. Data were collected from 5 school principals, 10 PAI teachers, and 50 high school students in [specify location] through participatory observation, in-depth interviews, and document analysis. Thematic analysis techniques, including data reduction, display, and conclusion drawing, were applied. The findings reveal that implementing technology-based innovations, such as digital applications and online learning platforms, significantly enhances learning effectiveness and motivates students. Moreover, aligning the curriculum with technological advancements fosters students’ digital literacy, spiritual development, and social competence. Practically, these findings offer actionable insights for educators, policymakers, and educational institutions. Teachers can adopt innovative digital tools to enrich the teaching process, while policymakers can design strategies to support the integration of technology into PAI curricula. Institutions are encouraged to invest in teacher training and infrastructure improvements to ensure the effective application of these innovations.